Cyanidin-3-O-glucoside enhances GLP-1 secretion via PPARβ/δ-β-catenin-TCF-4 pathway in type 2 diabetes mellitus - Xiang Ye; Wen Chen; Fujie Yan; Xiaodong Zheng; Pengcheng Tu (npj Science of Food)
Abstract In late-stage type 2 diabetes mellitus (T2DM), impaired islet β cell function leads to absolute insulin deficiency, thereby disrupting blood glucose homeostasis. GLP-1, an incretin hormone, stimulates insulin secretion from islet β cells post-meals. This study investigated the effects of anthocyanin cyanidin-3-O-glucoside (C3G) on GLP-1 secretion using STC-1 (intestinal endocrine L cells) and NIT-1 (islet β cells). In a co-culture system, C3G treatment increased GLP-1 secretion in STC-1 cells, promoting insulin release in NIT-1 cells under high glucose. Mechanistically, C3G activated the PPARβ/δ-β-catenin-TCF-4 pathway in STC-1 cells, enhancing PG precursor transcription and GLP-1 synthesis.Inhibiting PPARβ/δ with GSK0660 blocked this C3G-induced upregulation. Overall, C3G stimulates GLP-1 secretion from intestinal L cells via this pathway, indirectly boosting insulin release from β cells. These findings enhance T2DM mechanism understanding and suggest the potential of C3G in GLP-1-based T2DM therapy.